색채를 활용한 네일아트 연구 -현대미술사조의 작품을 중심으로 - 정시은; Si Eun; 정연자; Yeon Ja Jung (기초조형학연구, 2015)
뷰티디자인에서의 색채는 아름다움과 개성을 표현하는 기초재료로 사용되어지며 또한 뷰티디자이너에게 있어 색을 능숙하게 다룬다는 것이야말로 자신이 말하고자 하는 부분을 단순, 명료하게 표현하는 인상으로 남긴다. 자신만의 개성을 추구하는 포스트모던시대를 살아가는 현대인들에게 있어서 뷰티디자인은 조형예술의 한분야로 자리 잡아가고 있다. 따라서 본 연구에서는 문헌분석을 통해 현대 예술사조의 흐름을 살펴보고 색채가 감성을 표현하는 수단이 된 현대에 이르기까지 미술사조별 색채 경향을 분석하고 이를 적용한 네일아트 조형예술의 가능성을 제시하고자 하였다. 연구방법은 이론적 고찰을 위해 단행본이나 논문을 통해 현대 미술사조의 개념 및 특징을 분석하였고 사조별 작품의 색채 특징을 정리하였다. 실증적인 연구로써 현대미술의 특징이 잘 표현된 작품을 선정한 뒤 색채분석을 통해 얻어진 색채 데이터를 이용하여 모티브를 찾고 네일아트 디자인에 적용하여 작품을 제작하였다. 연구의 범위는 근대미술과의 혼동을 방지하기 위해 예술에 있어 자유로움과 무한한 상상력이 시작되던 1900년대 초를 기점으로 시작하였고 그 이후의 현대미술사조로 국한하여 설정하였다. 이러한 결과는 뷰티디자인에서의 창의적인 발상과 함께 무한히 활용할 수 있는 회화를 바탕으로 색채를 주제로 사용한 뷰티디자인의 교육적 자료로 활용할 것을 기대한다. Colors in the beauty design are used as basic materials to express beauty and personality, and for beauty designers, dealing with colors skillfully leaves the parts they would like to speak as impressions of simple and clear expressions. For modern people who pursue their own personalities, living in the post-modern era, the beauty design is being settled as an area of the formative arts. Thus, this study would look into the flow of the trend of contemporary art through literature analysis, analyze color trend by the trend of art through to the modern times when color has become a means of expressing sensibilities and present a possibility of formative arts of nail art applying this. Regarding research methods, for theoretical discussions, this study analyzed the concepts and characteristics of the trend of contemporary art through books or papers and organized color characteristics of works by the trend. As empirical research, works that express the characteristics of contemporary art well were selected, and then, using color data obtained through a color analysis, this study found motifs and applied them to nail art design to produce works. The scope of the study started from the early 1900s, when freedom and infinite began in the arts, in order to prevent confusion with modern art and was set up to the trend of contemporary art later on. It is expected that these results will be used as educational materials for the beauty design using colors as a subject based on paintings that can be used infinitely along with creative ideas in the beauty design.